Characteristic analysis and optimum management plan of disused sealed radioactive sources in Korea. (April 2017) - Kim, Juyoul; Kim, Sukhoon; Lee, Seunghee
Highlights: The optimum management plan of disused sealed radioactive sources (DSRS) in Korea was proposed. Three factors were considered based on the half-life of radionuclide, potential risk index and legal classification scheme of radioactive waste. It is expected that more safe and efficient management of DSRS could be provided based on the proposed procedure. Abstract: This study reviewed the current status of disused sealed radioactive source (DSRS) in Korea and analyzed its characteristics according to three factors, i.e., IAEA recommended classification system of radioactive waste based on the half-life of radionuclides, potential risk index based on activity divided by the corresponding radionuclide-specific 'D value' and legal classification scheme of radioactive waste based on the concentration of radionuclides. The optimum management procedure was derived based on above three factors above and applied to DSRS which are currently being stored in the centralized temporary storage facility for the radioisotope (RI) waste operated by Korea Radioactive Waste Agency (KORAD). The results of this study would be used as technical background document to draw up an optimum management plan of DSRS in the near future.